2008
DOI: 10.3736/jcim20080617
|View full text |Cite
|
Sign up to set email alerts
|

Electroacupuncture protects the brain against acute ischemic injury via up-regulation of delta-opioid receptor in rats

Abstract: EA can up-regulate DOR expression and protect the brain from ischemia-reperfusion injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 16 publications
1
22
0
Order By: Relevance
“…Unfortunately, although studies revealed that multiple EA improves neurological function in animal stroke models [14], there is less experimental evidence upon the underlying mechanisms of multiple EA treatment. Previous studies showed that multiple EA induces expression of Ang-1 and Ang-2 [15] and δ -opioid receptor [9] as well. However, whether multiple EA stimulation induces changes similar to those upon single-time EA stimulation?…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, although studies revealed that multiple EA improves neurological function in animal stroke models [14], there is less experimental evidence upon the underlying mechanisms of multiple EA treatment. Previous studies showed that multiple EA induces expression of Ang-1 and Ang-2 [15] and δ -opioid receptor [9] as well. However, whether multiple EA stimulation induces changes similar to those upon single-time EA stimulation?…”
Section: Introductionmentioning
confidence: 99%
“…DOR activation with DADLE also increases the tolerance of cultured cortical neurons against hypoxia [10]. Furthermore, we showed that DOR provides neuroprotection against hypoxic/ischemic insults in various models including neurons under hypoxia, brain slices in hypoxia or oxygen-glucose deprivation and in vivo brain exposed to cerebral ischemia [12,13,14,15,16,17,18,19,20,21,22,23]. Intracerebroventricular treatment with the DOR agonist TAN-67 (60 nmol) significantly reduced the infarct volume and attenuated neurological deficits, while Naltrindole, a DOR antagonist, aggravated ischemic damage after forebrain ischemia in rats [12].…”
Section: Introductionmentioning
confidence: 99%
“…Electroacupuncture can also upregulate DOR expression in the ischemic brain and thus protect the brain from ischemic injury [15] that can cause epilepsy secondary to cerebral infarction [74]. Most interestingly, direct subacute high-frequency electrical stimulation of the parahippocampal cortex in patients with intractable medial temporal lobe epilepsy also produces an antiepileptic effect, which is associated with reduced opioid peptide binding including 3 H-DAMGO, 3 H-DPDPE, and 3 H-nociceptin (the ligand for MOR, DOR, and a fourth opioid, nociception receptor, resp.)…”
Section: Potential Mechanisms Of Acupuncture Inhibition Of Neuronamentioning
confidence: 99%
“…Some acupuncture-induced effects involve the activation of the opioid system [813]. We have previously demonstrated that electroacupuncture has a neuroprotective role in the brain against ischemic injury via the δ -opioid system [14, 15]. DOR expression/activation inhibits Na + channel activity [16, 17] and thus attenuates Na + -K + homeostasis of the cortex under normoxic/hypoxic conditions [16, 1822].…”
Section: Introductionmentioning
confidence: 99%